Effect of the Galling Aphid of Baizongia pistaciae L. on Composition and Biological Activities of Essential Oils of Pistacia atlantica Desf. Growing Wild in Jordan. Issue 3 (4th May 2017) - Awwad, Oriana; Abu-Dahab, Rana; Abaza, Ismail F.; Alabbassi, Reem; Majdalawi, Lara; Afifi, Fatma U.
Abstract: Aqueous extract of Pistacia atlantica leaves is widely used in Jordanian traditional medicine for management of diabetes. The genus Pistaciae serves as obligate host for a group of specialized gall-forming aphids. The present study aimed to identify the aphid attacking P. atlantica trees growing wild in Jordan, to determine the composition of the essential oils from leaves and galls (fresh and dry) and to investigate the antiproliferative activities of the traditionally used dry plant on colon and breast cancers. Hydro-distillation of the essential constituents of P. atlantica leaves was performed and their composition determined. The antiproliferative activity of leaf and galls oils, doxorubicin, and six pure components (sabinene, limonene, α-pinene, β-pinene, α-terpinene, and γ-terpinene) were investigated against two colon (Caco-2 and HCT116) and two breast cancer cell lines (MCF7 and T47D) by MTT assay. Fresh leaf showed the greatest variation in the constituents' composition. Low molecular weight monoterpene hydrocarbons were the major constituents of both tested organs. The highest percentage of sesquiterpenes was observed in fresh leaf oil, with γ-muurolene as the major component. Tested components exhibited differences in their toxicity against the cell lines under experiments. Cytotoxic effect of doxorubicin was enhanced by the addition of P. atlantica leaf oil but not galls oil. Our findings demonstrated qualitative and quantitative diversity in the composition of the P. atlantica oils. The oils exhibited differences in the antiproliferative activity against colon and breast cancer cell lines. Further molecular experiments are needed to explain such differences.